2007
DOI: 10.1108/02632770710742192
|View full text |Cite
|
Sign up to set email alerts
|

A review and classification of academic research in facilities management

Abstract: Purpose -The purpose of this paper is to review, evaluate and classify the academic research that has been published in facilities management (FM) and to analyse how FM research and practice are linked. Design/methodology/approach -This paper is based on literature review and qualitative research. Qualitative data have been gathered from academic papers published in FM-related journals (i.e. Facilities, Journal of Facilities Management, and the Nordic Journal of Surveying and Real Estate Research -Special Seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 29 publications
(31 reference statements)
0
40
0
Order By: Relevance
“…Some researchers advocated that FM needed to 'be more closely aligned to a management discipline ' (McLennan, 2004, p. 344) to stand out and suggested that the Service Management theory would be of use to FM research. Other researchers started to call for a stronger link between research and practice to promote FM (Ventovuori et al, 2007). Nutt (1999) suggested that areas of special interest for future collaborative research (between FM practice and FM research) would be managing facility operations and support services.…”
Section: The Rise Of Fm In Practice and Research -The 1980smentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers advocated that FM needed to 'be more closely aligned to a management discipline ' (McLennan, 2004, p. 344) to stand out and suggested that the Service Management theory would be of use to FM research. Other researchers started to call for a stronger link between research and practice to promote FM (Ventovuori et al, 2007). Nutt (1999) suggested that areas of special interest for future collaborative research (between FM practice and FM research) would be managing facility operations and support services.…”
Section: The Rise Of Fm In Practice and Research -The 1980smentioning
confidence: 99%
“…Having emerged over the last 30 years, FM as a field of research and practice is considered to be a relative new profession with particularly rapid development since the 1990s (Jensen and Nielsen, 2012;Ventovuori et al, 2007;McLennan, 2004;Amaratunga et al, 2002;Tay and Ooi, 2001;Nutt, 1999;Spedding, 1994); thus, FM has been defined in several ways over the years (Spedding, 1994;Tay and Ooi, 2001). It is hoped that a global agreement on how to define this field will soon be reached.…”
Section: Defining Fmmentioning
confidence: 99%
See 1 more Smart Citation
“…Undoubtedly, a large body of literature on facilities management exists (see, eg Ventovuori et al ., 2007 ) investigating a wide range of topics.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…A number of study conclusively revealed that, after commissioning of a building, the principle role of a FM personnel is the change of this physical item into a suitable, reasonable and habitable built environment for the owner and end user ( [8], [9]). In particular, this condition should be maintained through the lifespan of building services.…”
mentioning
confidence: 99%